KARAKTERISTIK DAN FAKTOR SENGKETA DESAIN INDUSTRI DENGAN BENTUK PENYELESAIANNYA - Febry Chrisdanty; Diah Wahyulina (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2026)
Industrial design is a form of intellectual property that is closely linked to people’s lifestyles, as every product created takes into account not only functionality but also user preferences, comfort, and aesthetic appeal. Social, cultural, and technological trends influence the development of industrial design, serving as a source of inspiration for designers in creating relevant and sought-after products. However, the proliferation of these ideas presents challenges for new designers, as there is a risk of designs resembling previous ones. This is often the root cause of disputes with specific characteristics. This study aims to analyze how industrial design characteristics can influence the emergence of factors causing disputes, as well as the factors causing disputes that can be used to determine the most effective form of resolution. This empirical legal study employs an interview approach and the distribution of questionnaires. The results of the discussion indicate that the characteristics of industrial design disputes can influence the identification of the factors causing such disputes, including: the novelty of the protected object; a lack of understanding regarding industrial design; the evidence held by the parties; public awareness; and economic factors. Furthermore, these causal factors influence the selection of dispute resolution mechanisms, which in Indonesia can be pursued through litigation in the Commercial Court or through non-litigation avenues such as mediation, arbitration, and negotiation. Non-litigation resolution is considered more effective for resolving disputes related to business interests and commercial relationships, whereas litigation is more appropriate for disputes requiring legal certainty and the firm enforcement of rights. Understanding the characteristics and factors causing industrial design disputes is crucial in determining a resolution method that is efficient, fair, and provides legal certainty for the parties involved. Keywords: industrial design, welfare, intellectual property, resolution, legal protection.